Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004073.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin supplementation for preventing miscarriage

Abstract: Taking vitamin supplements, alone or in combination with other vitamins, prior to pregnancy or in early pregnancy, does not prevent women experiencing miscarriage or stillbirth. However, women taking vitamin supplements may be less likely to develop pre-eclampsia and more likely to have a multiple pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 98 publications
0
19
1
2
Order By: Relevance
“…The latest Cochrane database review on vitamin supplementation for preventing miscarriage concluded that taking any vitamin supplements prior to pregnancy or in early pregnancy does not prevent women experiencing miscarriage or stillbirth. On the other hand they admit that there is insufficient evidence to examine the effects of different combinations of vitamins on miscarriage, stillbirth or other maternal and infant outcomes [29]. In our study levels of vitamin C and markers of oxidative stress were similar in the two normal pregnancy groups which may be a consequence of a healthy diet in the not treated arm, but also a lack of beneficial effects of the supplement in question.…”
Section: Resultscontrasting
confidence: 49%
“…The latest Cochrane database review on vitamin supplementation for preventing miscarriage concluded that taking any vitamin supplements prior to pregnancy or in early pregnancy does not prevent women experiencing miscarriage or stillbirth. On the other hand they admit that there is insufficient evidence to examine the effects of different combinations of vitamins on miscarriage, stillbirth or other maternal and infant outcomes [29]. In our study levels of vitamin C and markers of oxidative stress were similar in the two normal pregnancy groups which may be a consequence of a healthy diet in the not treated arm, but also a lack of beneficial effects of the supplement in question.…”
Section: Resultscontrasting
confidence: 49%
“…Although several small-scale studies have indicated that the use of anti-inflammatory agents (aspirin) or anti-oxidants (vitamin C and E) may be beneficial if given early in pregnancy before the onset of symptoms, this remains to be confirmed in large-scale analyses [88].…”
Section: Therapeutic Possibilitiesmentioning
confidence: 99%
“…Indeed, although obstetricians have been using vitamin E for years in the hope of preventing abortion (SHUTE 1960), there is no evidence that taking antioxidant vitamin supplements, alone or in combination with other agents, prior to pregnancy or in early pregnancy, prevents miscarriage (Rumbold et al 2005). So, further studies are needed.…”
Section: Spontaneous Miscarriage and Recurrent Pregnancy Lossmentioning
confidence: 99%